Power output prediction of a Photovoltic module (PV) using artificial neural network - محمد العزوزي, طليبة; عبد العالي, بن عبد الله; معاذ, . سلاطنة; هشام, بن عمر (University of El-Oued, 2022)
"Abstract: In present work, a solar power modelling using artificial neural networks (ANN) is presented, for a precise prediction of generated output power of a PV module. Prediction process plays an essential aspect in many sectors of power system like in solar energy sources which is the current topic being discussed. Output power for solar energy system is a tough parameter to be predicted due to the influence of numerous parameters, fluctuations and due to the fact that parameters are dependent on each other which produces the nonlinearity problem. In this study, ambient conditions of PV module temperature, solar radiation, wind speed and ambient temperature are collected and then introduced to an artificial neural network to predict the output power. Finally, after this study, we concluded that the artificial neural network has a good and accurate prediction ability, despite its difficulty" "الخلاصة: في العمل الحالي ، تم تقديم نمذجة الطاقة الشمسية باستخدام الشبكات العصبية الاصطناعية (ANN) ، من أجل التنبؤ الدقيق للطاقة الناتجة الناتجة عن وحدة PV. تلعب عملية التنبؤ جانبًا أساسيًا في العديد من قطاعات نظام الطاقة مثل مصادر الطاقة الشمسية وهو الموضوع الحالي الذي تتم مناقشته. تعد طاقة الخرج لنظام الطاقة الشمسية معلمة صعبة يمكن التنبؤ بها بسبب تأثير العديد من المعلمات والتقلبات وبسبب حقيقة أن المعلمات تعتمد على بعضها البعض مما ينتج عنه مشكلة غير خطية. في هذه الدراسة ، يتم جمع الظروف المحيطة لدرجة حرارة الوحدة الكهروضوئية والإشعاع الشمسي وسرعة الرياح ودرجة الحرارة المحيطة ثم إدخالها إلى شبكة عصبية اصطناعية للتنبؤ بالطاقة الناتجة. أخيرًا ، بعد هذه الدراسة ، توصلنا إلى أن الشبكة العصبية الاصطناعية تتمتع بقدرة تنبؤ جيدة ودقيقة ، على الرغم من صعوبة ذلك"
مذكرة ماستر تخصص كهروميكانيك
Keywords: "Réseau de neurones artificiels (ANN); module photovoltaïque (PV); prédiction; Puissance"; الشبكة العصبية االصطناعية- الوحدة الكهروضوئية- التنبؤ- الطاقة